Latin America and the construction of a hegemonic periodization. - Riojas López, Carlos (Ciencia Nueva, revista de Historia y Política, 2019)
Underlying institutional factors and a type of periodization in the most influential narratives of global history contribute to the peripheralization of Latin America. The objective of this article is to learn more precisely what is being written about Latin America in two leading journals that study this continent as their main topic. I have chosen five periods and four historical events. Even though the periodization is constructed by events linked to the trajectory of the West, it offers an opportunity to situate Latin America as a key actor in a new global history.